Access to stroke care in Europe: results of a vignette approach. (20th October 2021) - Quentin, W
Abstract: Background: Stroke is a major cause of death and disability in Europe. European guidelines for patients with ischemic stroke (about 85% of all strokes) recommend rapid access to hospital care and rehabilitation after discharge from hospital. Information on access to stroke care in Europe is limited. Methods: A stroke vignette was developed reflecting typical patient characteristics and a recommended patient pathway: ambulance transfer to hospital, fast-track diagnostic work-up, thrombolysis and mechanical thrombectomy, stroke unit treatment, and inpatient rehabilitation. Experts in 12 countries were asked to complete a survey on service coverage, cost sharing, physical access (availability) and other barriers to access. Survey results were analysed and access to services was categorized into good, medium, bad before summarizing results across countries. Results: Completed surveys were received from ten countries, including Bulgaria, Estonia, France, Germany, Lithuania, the Netherlands, Poland, Portugal, Slovakia, and the UK (England). Stroke patients in France, Germany, and the Netherlands have relatively good access, while substantial barriers exist in Bulgaria, Estonia, Poland, and Slovakia. In Bulgaria, rehabilitation is not covered by the National Health Fund; and rehabilitation capacity is very limited in Estonia, Poland, and Slovakia, leading to limited access. Almost all recommended services are formally covered by public financing schemes, but insufficient availability or organisational problems limit access to thrombolysis in Bulgaria, France, Lithuania, Poland, and Portugal or thrombectomy in Bulgaria and the UK (England). Conclusions: While stroke related services are formally covered in almost all countries, considerable access problems exist in several countries. Future cross-country surveys of access to stroke care should collect quantitative data related to proportions of patients receiving particular services as well as qualitative data on access barriers.